Regional control structures of kimberlite emplacement in the southern São Francisco Craton basement: A multidisciplinary approach including a representative example from Junco diatreme (Divinópolis, MG, Brazil) - Silva, Francisco José da; Barros, Renato de Assis; Clemence Junior, George William [UNESP]; Gomes, Diego Guilherme da Costa; Bertolino, Luiz Carlos; Marques, Eduardo Duarte (Elsevier, 2022)
In the southernmost São Francisco Craton, the well-exposed Archean to Paleoproterozoic basement shows kimberlite bodies that represent the last southeastern clusters associated with the Azimuth 125° structure. The absence of Mesozoic to Cenozoic overlying cover rocks in the region allows in-depth aeromagnetic geophysical interpretation of the structural controls responsible for the emplacement of kimberlites. The main controlling structures are depicted by the crosscut NW-SE dyke swarms of Paraopeba, Pará de Minas, and Transminas with the E-W lineaments, characterized by quartz veins and hydrothermalites in the area. The Junco kimberlite intrusion occurs in the region, and reproduces some regional controls at a local scale: the ascent mechanism along a mafic dyke (Pará de Minas swarm) and the placement in the intersection of the mafic dyke with E-W structures. Geological mapping confirmed the remote interpretation and defined the intrusion as oval-shaped, with the magnetic model indicating a bulky diatreme body up to 500 m depth. The goal of this research is to show the importance of the regional controls, their relation to the Junco intrusion, and combine aerogeophysical analysis, geological mapping, mineral chemistry, and lithosphere information to unravel potentially linking processes operating at variable scales. In this context, regolith material overlying the intrusion was sampled, and the indicator minerals pyrope garnet, clinopyroxene, ilmenite, and chromite were selected and analyzed for mineral compositions using electron probe microanalysis. Pyrope garnet and chromite do not show a relation to diamond's potential fields. Ilmenite analyzes indicate relatively high level of oxidation, a characteristic that differentiates the Junco diatreme from kimberlites occurring in the Alto Paranaíba Igneous Province within the southern Brasília Fold Belt. Single-clinopyroxene thermobarometry calculations provided pressure-temperature array values ranging from 745 °C to 832 °C and 31.3 kbar to 38.9 kbar, respectively. A geotherm model was fitted resulting in an estimated surface heat flow of 49.0 mW/m2 and a lithospheric thickness of 202 km. The average equilibration depth of the clinopyroxene at 99.6 km points to pressure-temperature conditions consistent with the stability field of graphite.
Keywords: Indicator geochemical signatures; Junco kimberlite; Magnetic lineaments; Regional control structures; Thermobarometry